Pelaksanaan Tata Kelola Administrasi Data Kesiswaan Di Madrasah Tsanawiyah Darul Jannah Muara Burnai II - Kms Badarudin; Saipul Annur; B Santoso (Studia Manageria, 2021)
This study aims to see how far the system of implementing administrative governance is at Madrasah Tsawawiyah Darul Jannah Muara Burnai II, Ogan Komering Ilir Regency. This study aims to analyze, and describe the process of implementing the administrative governance of Ogan Komering Ilir Regency. The data collection technique uses observation, interviews, and documentation studies, and the data analysis uses reduction, data display, and drawing conclusions. The results obtained include the implementation of administrative governance at MTs Darul Jannah Muara Burnai II, through the planning process and service improvement carried out by the madrasa administration manager by analyzing the needs of madrasa residents at the end of each semester. make data on the submission of madrasa needs, in coordination with the head of the madrasa, then the manager and the head of the madrasa find the services needed. The inhibiting factors are the lack of infrastructure, personnel who are not in accordance with their educational background, and the rules that often change. while the supporting factors are, the existence of adequate resources, a conducive work climate and full of kinship, motivation, a high sense of responsibility, and dedication to work.